Production of Bio-fuel (Bio-Ethanol) from Biomass (Pteris) by Fermentation Process with Yeast - Khan, Maksudur R.; Saha, Pradip; Fakhrul Alam, Md.; Baishnab, Ajit Chandra; Islam, M. A. (Science and Education Publishing, 2014)
Bio-Ethanol is a renewable; eco-friendly energy source can be produced from bio-mass (hemicelluloses). Pteris (fern) is grown very fast and has not major economic importance but it is a reliable source of hemicelluloses can be converted to bio-Ethanol. In the hydrolysis of hemicelluloses the concentration of glucose and the reaction rate was observed with respect to the different parameters, like pH, temperature, substrate diameter, substrate loading. In this study we found optimal parameters, NH4OH treatment as the best treatment among H2SO4, NH4OH, and NaOH treatment. In addition, pH 7, temperature 35°C, substrate diameter 45μm-63μm, and substrate loading 0.25gm in 100ml working volume was found as optimum operation condition for hydrolysis reaction, which was carried out by pseudomonas sp., isolated from cow dung. In this experiment sugar concentration was measured with UV spectrophotometer using DNS reagent finding the equilibrium time is 72hours for hydrolysis process and the maximum sugar concentration of 1.7625mg/l was achieved. Subsequently we study the fermentation process using yeast to produce Bio-Ethanol from reducing sugar solution obtained from the hydrolysis process on optimum reaction condition and yield the Ethanol concentration 0.333 mg/L, measured with UV spectrophotometer. Furthermore, it was also observed that the activity of yeast was sustain, in the reaction condition (pH = 7, temperature = 25°C), only for 50 hours. In sum, it could be conclude that 0.1332 mg of ethanol can be produce from 1gm of pteris where the conversion of reducing sugar to ethanol is 20% approximately in the optimum reaction condition.